The Relationship Of Mother Characteristics With Exclusive Assessment - Sari, Iramaya; A.Tenri Fajriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
World Health Organization (WHO) recommends a mother to give breast milk (ASI) exclusively. Exclusive breastfeeding is breastfeeding for infants up to 6 months of age, without the addition of fluids and solid food. Exclusive breastfeeding in various regions is still low. The purpose of this study is the relationship of maternal characteristics (age, parity, education, occupation) with exclusive breastfeeding in the working area of ​​Caile Health Center, Ujung Bulu District, Bulukumba Regency. The type of research used in this study is Analytical Observational, which is a researcher trying to find the relationship between variables. By using a cross-sectional approach. In this study, the sampling technique carried out by the author is the consecutive sampling method in which a sample selection method is done by selecting all individuals who meet and meet the selection criteria with a total sample of 37 people. There is no relationship between mother's work and exclusive breastfeeding in the Caile Community Health Center in Ujung Bulu District, Bulukumba Regency with a P-Value of 0.317. The conclusion is for working mothers to still be able to give their babies exclusively breastfeeding the right way. When the mother is sick, she should still be able to give the baby exclusively.